Estrogen leads to reversible hair cycle retardation through inducing premature catagen and maintaining telogen. - Hui-min Hu (Public Library of Science (PLoS), 2012)
Estrogen dysregulation causes hair disorder. Clinical observations have demonstrated that estrogen raises the telogen/anagen ratio and inhibits hair shaft elongation of female scalp hair follicles. In spite of these clinical insights, the properties of estrogen on hair follicles are poorly dissected. In the present study, we show that estrogen induced apoptosis of precortex cells and caused premature catagen by up-regulation of TGF β2. Immediately after the premature catagen, the expression of anagen chalone BMP4 increased. The up-regulation of BMP4 may further function to prevent anagen transition and maintain telogen. Interestingly, the hair follicle stem cell niche was not destructed during these drastic structural changes caused by estrogen. Additionally, dermal papilla cells, the estrogen target cells in hair follicles, kept their signature gene expressions as well as their hair inductive potential after estrogen treatment. Retention of the characteristics of both hair follicle stem cells and dermal papilla cells determined the reversibility of the hair cycle suppression. These results indicated that estrogen causes reversible hair cycle retardation by inducing premature catagen and maintaining telogen.